Serious Game to Training Focus for Children with Attention Deficit Hyperactivity Disorder: “Tanji Adventure to the Diamond Temple” - Raden Bagoes Yudha Rangga Sanjaya; Rahadian Kurniawan; Sri Mulyati; Kukuh Eka Nugraha Chrisna Putra; Restu Rakhmawati (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) affects the academic performance of youngsters. Children with ADHD struggle to remain focused during learning due to decreased attention and concentration. They are highly active and have trouble remembering teachers' instructions. Attention difficulties, focus disorders, and hyperactivity might hinder learning. This work aims to observe the impact of serious games with a platformer genre and puzzles titled